A high frequency investigation during a financial crash - Soytaş, Mehmet Ali (My University, 2005)
Bu tez Piyasa Mikroyapısını teorik ve ampirik perspektiflerden incelemektedir. Teorik kısımda, Piyasa Mikroyapısı konusunda yapılan teorik katkılar gözden geçirilmiş ve piyasa mikroyapısının temel özellikleri ve onu oluşturan büyüklükler açıklanmıştır. Ampirik bölümde, İstanbul Menkul Kıymetler Borsası'ndan elde edilen DEMİRBANK hisse senedine ait data kullanılarak gün içi hisse senedi özellikleri incelenmiştir. Demirbank hissesinin 06 Aralık 2000 tarihinde bankanın repo piyasasında yaşanan kriz sonucu batmasıyla artık işlem görmemesi, bu hissenin gün içi hareketlerini hem kriz hem de kriz dışında inceleme fırsatı vermiştir. Elde edilen sonuçlar Demirbank hisse senedinin literatürde başka piyasalar için yapılan çalışmalarla çoğunlukla benzerlik gösteren yönleri olduğunu, fakat aynı zamanda farklı gün içi hareketleri de olduğunu göstermiştir. Bu faklılıklar İstanbul Menkul Kıymetler Borsası'nın yapısından kaynaklanan farklılıklar ve Demirbank hisse senedinin özelliklerinden kaynaklanmaktadır. Demirbank hisse senedinin durasyon datası ekonometrik tahmin için kullanılmıştır. Tahmin edilen modeller, Engle and Russell (1998) ACD Modeli ve Bauwens ve Giot (1998) modelidir. Sonuç olarak bulunan, ACD(2,2) modelinin performanısı diğer modellerden üstündür. In this thesis microstructure models both in theoretical and empirical aspects are tried to be examined. On the theoretical side, it is aimed to provide a general survey of the main theoretical models in the microstructure literature, and the hallmarks of microstructure area. On the empirical size, we used the Demirbank's stock data provided by Istanbul Stock Exchange to investigate the intra-daily properties. Considering the fact that after 05 December 2000, the stock was no longer traded after the default of Demirbank on 6th December in the Turkish overnight market crises; the data is investigated in two periods, tranquil and crises. First of all the intra-daily data is used to highlight the high frequency properties of Demirbank's stock during the tranquil period, and then to catch the differences in the intra-day properties during the crises period. Empirical work can be viewed as a verification of the well known patterns in intra-day stock data; such as U-shaped volume etc., however there are significant distinctions that can be attributed to Demirbank's stock or the structure of Istanbul Stock Exchange. The duration series obtained from Demirbank's stock is used for the econometric estimation where (ACD) model of Engle and Russell (1998) and LACD model of Bauwens and Giot (1998) are estimated. ACD(2,2) model is found to be superior to other specifications.
Keywords: Hisse Senetleri; Mali Krizler